Prediction analysis of academic dropout in students of the Pablo de Olavide University - Cuevas López, Mercedes; Díaz-Rosas, Francisco; Díaz-Mohedo, María Teresa; Vicente-Bújez, Manuel Ricardo (Frontiers in Education, 2023)
This preliminary study presents an approach to the phenomenon of academic failure at the Pablo de Olavide University in Spain through the determination of the factors linked to students continuing with their studies, and the subsequent establishment of risk groups. The study consisted of applying an instrument to diagnose the risk of academic dropout among a sample of 70 students from the Pablo de Olavide University (from now on, UPO). For this purpose, we used the survey about successfully keeping students conducted by Velázquez and González (2017) with a slight modification in the wording of some items in the survey to adapt them to the reality of Spanish students. The instrument was applied at the beginning of the second semester. Unlike the objective posed by the aforementioned authors (the search for factors linked to students continuing their university studies), the use that we made of the survey was to predict non-persistence (dropout). The average overall score achieved for all of the items allows us to confirm that the student population surveyed seems to be more oriented to continuing with their studies than dropping out, although 15.71% of them show a high risk of dropping out, and most notably more than half of those taking a degree in Business Studies present this high level of risk. Unlike the results obtained by Velázquez and González (2017), in whose study there was no significant correlation noted between motivation and persistence, in the case of the UPO students the direct associations between the independent variables regarding the dependent variable were present in all of the factors (attitude and behaviour, commitment, socio-economic background, and motivation) with a p-value lower than 0.05 Comparing these data to those obtained by Álvarez et al. (2022) with students from different universities in Andalusia, it was found that the risk groups of UPO students are less inclined to dropping out than those from other universities, and their level of commitment is lower, although their attitude and behavior are somewhat better. Finally, socio-economic background is a less significant factor for UPO students.